Challenges Encountered and Technical Assistance Needed by Parents and Learners Utilizing Modular Distance Learning: Basis for a Proposed Support Program - A. Bayucca, Shallimar (Journal of Humanities and Social Sciences (JHASS), 2021)
The shift from face-to face to distance learning brought about by the outbreak of the COVID-19 pandemic is a major adjustment to all school administrators, teachers, students and parents. The study aimed to determine the challenges encountered and needed support of parents and learners in an elementary school of the Schools Division of Meycauayan City as basis for crafting a contextualized support program. It employed a mixed method design using survey-questionnaire and interview guide as data gathering tools to 123 parents and 10 learners respectively. Frequency and percentage were used to describe the demographic profile, frequency counts and ranking were used on the challenges encountered and support/technical assistance needed by parents while thematic analysis was used to describe the experiences of the learners. The study found out that difficulty in independent learning, difficulty in concentrating on studies and parent’s limited knowledge on the content of child’s lessons are the top struggles of parents in the modular distance learning while almost all learner-respondents describe their experiences of distance learning as difficult because of difficulty in learning by themselves, lack of reference materials for more examples, limited guidance from parents and teachers, challenges in load to research and difficulty in understanding English. Moreover, both respondents are unanimous in declaring that provision of additional reference materials will greatly help lessen the struggles they encountered. Therefore, it is recommended that the support program crafted should be implemented and monitored to fully reinforce the continuity of learning amidst the challenges encountered in the first quarter.